CHICANA EXPERIENCE IN DENISE CHVEZS FACE OF AN ANGEL : A FEMINIST PERSPECTIVE - Ni Luh Putu Rosiandani (Soegijapranata Catholic University, 2006)
This study is an attempt to examine the experience of three generations of Chicana, women of Mexican descent in the United States, which is viewed from feminist perspective. The purpose of this study is to reveal the changing perspective of Chicanas toward their feminine identity that has been established by patriarchal Mexican and Catholicism cultures. The result of the study shows that the awareness on feminism existed in each generation stimulates the changing perspective toward the constructed feminine identity.